Розробка обчислювальних методів для застосування в грі Star crafted crossroad - Дуванов, А. К. (ХНУРЕ, 2024)
This work is devoted for deriving computational methods for the purpose of creating an engaging and interactive game process with the usage of these methods, which are meant to get the needed situational values. The main stages of requirements and descriptions of these methods are considered. Implementation, demonstration and explanation of practical appliance of these computation methods in game environment are provided.
Keywords: обчислювальний метод; game; Star crafted crossroad